The Construction of Musical Instruments - Kuzmič , Maja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the creation of musical instruments in primary schools using various materials. Musical instruments are defined as devices that enable music performance and are categorized based on their acoustic properties and methods of play. The process of crafting instruments promotes cognitive, physical, and motor development in students, while also bringing joy through the creation of functional products. Teachers are encouraged to plan active lessons that incorporate the use of diverse materials for students to explore and create with. These materials may include paper, wood, metal, synthetic substances, or even everyday objects such as stones or grains. The chapter highlights a good practice example from Ankara, where schools and kindergartens began making instruments themselves due to financial constraints. Through this process, students acquire not only practical knowledge but also invaluable experiences that cannot be gained by simply purchasing professional instruments.